Increasing Employment Levels in Infrastructure Development Projects - Rifat Rustom; Tareq Assar (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
A new approach is suggested to be applied to increase employment in infrastructure development projects. The proposed approach moderates the usually capital-intensive (equipment-based) infrastructure development to make it more responsive to short-term employment needs. The proposed higher labor-content project cycle emphasizes stronger project planning, preparation, and participation of the involved community in all project phases, including the design phase, and reconsiders, inter alia, the basis for awarding contracts so as to increase employment levels (labor content) in infrastructure development projects. The proposed approach also introduces new reporting requirements and enhances learning through emphasizing project final evaluation.